Do Business Graduates Intend to Adopt the Social Business Model? A Perspective of Developing Country. Issue 1 (June 2020) - Hossain, Muhammad Ismail; Akter, Nasrin
Social business model (SBM) although presumed to be a saviour of businesses and the world in terms of reach, frequency and impact on society, is yet to be adopted by countries around the world including the developing countries, which potentially could enjoy the greatest benefits from adopting this business model. This study contributes to this end by testing the adoption intention of SBM by applying the theory of planned behaviour from a developing country perspective that happens to be the birthplace of SBM. Drawing on the data collected from the largest university of a developing country that houses over 40, 000 students and the future business leaders, this paper presents the underlying psychological drivers behind adopting SBM. Findings show that SBM adoption intention is facilitated by attitude and subjective norms; however, constrained by perceived behavioural control, which contrasts the existing entrepreneurial intention-based findings. Explanations and implications of such findings are provided.